Political reconfiguration in the social space: data analysis and future perspective - Battista, Daniele (Frontiers in Sociology, 2024)
This contribution aims to explore the complex and at times controversial relationship between social media and politics. The correlation between these two areas of research has always been less linear than a simplistic narrative might suggest, especially due to the involvement of different scientific disciplines. The decision to delve into this topic is motivated by the persistent relevance of social media platforms in the current era. This growing centrality is also due to the acceleration of the digitization process that occurred during the pandemic phase in the digital ecosystem. In particular, the pandemic has contributed to a significant evolution around the concept of social networks. The work seeks to highlight the expansion of the digital space resulting from the transition from a simple place of interaction to a digital space that has reconfigured the mobilization and political action of Campania Governor Vincenzo De Luca. In other words, it becomes necessary to ask and understand whether the potential of new social technologies is being used to cultivate critical and massive citizen participation in democratic processes, or if it is being distorted solely for the purpose of increasing or consolidating one's own consensus.The research analyzes the interaction between social media and politics, examining how these tools influence political communication and democratic participation. It highlights the societal changes related to the commercialization of communication and discusses the role of social media in engaging citizens who are distant from politics. It emphasizes that if used ethically and responsibly, social media can foster inclusive and informed democratic participation. The case of the Campania governor Vincenzo De Luca is also referenced to illustrate how the transition to digital spaces has reshaped political action during the pandemic.Generated Statement: No animal studies are presented in this manuscript.Generated Statement: No human studies are presented in this manuscript.Generated Statement: No potentially identifiable human images or data is presented in this study.